ANALISIS PENGARUH STRUKTUR KOTA - SISTEM TRANSPORTASI - KONSUMSI BBM KOTA-KOTA DI JAWA - Handajani, Mudjiastuti (Semarang State University, 2010)
Abstract:ÃÂ TransportationÃÂ ÃÂ ÃÂ sectorÃÂ isÃÂ sector withÃÂ the mostÃÂ customerÃÂ fuel,ÃÂ soÃÂ fuelÃÂ consumptionÃÂ for transportationÃÂ activityÃÂ shouldÃÂ appropriatelyÃÂ ÃÂ ÃÂ getÃÂ moreÃÂ attention.ÃÂ TheÃÂ increasingÃÂ activityÃÂ of transportation syatem especiallyÃÂ triggered byÃÂ theÃÂ increase of ownership and private vehicle usagegive negative impacts on towns. Ttransportation is sector taking the most fuel got from fossil source whichÃÂ is gettingÃÂ rare and unrenewable. Data collectedÃÂ inÃÂ thisÃÂ researchÃÂ is: a) data ofÃÂ length ofÃÂ the road,ÃÂ theÃÂ lengthÃÂ ofÃÂ theÃÂ road,ÃÂ onlyÃÂ calculatedÃÂ forÃÂ asphaltedÃÂ roadÃÂ orÃÂ reinforcedÃÂ concrete,ÃÂ b)ÃÂ road network pattern,ÃÂ ÃÂ in the field condition, road network patternÃÂ ÃÂ does not always have the same form asÃÂ roadÃÂ networkÃÂ patternÃÂ inÃÂ theÃÂ theory,ÃÂ ofÃÂ (grid,ÃÂ radial/concentric,ÃÂ linear),ÃÂ butÃÂ thereÃÂ areÃÂ some modifications, c)ÃÂ road condition, consisting of good,ÃÂ relatively good, poor, and very poor condition category,ÃÂ d)ÃÂ passengerÃ¢â¬â¢sÃÂ publicÃÂ transportation,ÃÂ consistingÃÂ ofÃÂ publicÃÂ passengerÃÂ transportationÃÂ and publicÃÂ bus,ÃÂ e)goosÃÂ transportation/truck,ÃÂ f)ÃÂ privateÃÂ vehicleÃÂ consistingÃÂ ofÃÂ passengerÃÂ car,ÃÂ busÃÂ and motorcycle, g)ÃÂ theÃÂ length of designatedÃÂ route of publicÃÂ transportation. The highestÃÂ influence ofÃÂ the townÃÂ structureÃÂ onÃÂ fuelÃÂ consumptionÃÂ isÃÂ theÃÂ numberÃÂ ofÃÂ people,ÃÂ thatÃÂ isÃÂ 0,986.TownÃÂ transportation systemÃÂ alsoÃÂ hasÃÂ theÃÂ highÃÂ influenceÃÂ valuesÃÂ onÃÂ fuelÃÂ consumption,ÃÂ thatÃÂ isÃÂ 0,907.ÃÂ TownÃÂ structure stronglyÃÂ influencesÃÂ fuelÃÂ consumptionÃÂ isÃÂ strongerÃÂ comparedÃÂ toÃÂ theÃÂ transportationÃÂ systemÃÂ onÃÂ fuel consumption. Key word:ÃÂ influence, town structure, transportation system, fuel consumption. ÃÂ Abstrak:ÃÂ SektorÃÂ transportasiÃÂ merupakanÃÂ konsumenÃÂ yangÃÂ palingÃÂ banyakÃÂ menggunakanÃÂ BBM, sehingga konsumsi BBM untuk kegiatan transportasi selayaknya mendapat perhatian. Peningkatan kegiatan sistemÃÂ transportasi khususnya yang dipicu oleh peningkatan pemilikan dan penggunaan kendaraan pribadi memberikan dampak negatifÃÂ terhadap kota. Transportasi merupakan penyerap bahanÃÂ bakarÃÂ terbesarÃÂ yangÃÂ berasalÃÂ dariÃÂ sumberÃÂ fosilÃÂ yangÃÂ semakinÃÂ langkaÃÂ danÃÂ tidakÃÂ dapat diperbaharui. Data yang dikumpulkan dalam penelitianÃÂ ini adalahÃÂ : a) data panjangÃÂ jalan, panjang jalan, dihitung hanyaÃÂ jalan yang aspal atau beton bertulang saja b) polaÃÂ jaringanÃÂ jalan, kondisi di lapangan polaÃÂ jaringanÃÂ jalanÃÂ tidak selalu membentuk persis seperti polaÃÂ jaringanÃÂ jalan dalamÃÂ teori (grid,ÃÂ radial/konsentrik,ÃÂ linear)ÃÂ tetapiÃÂ adaÃÂ beberapaÃÂ modifikasiÃÂ c)ÃÂ kondisiÃÂ jalanÃÂ yangÃÂ terdiriÃÂ dari kondisi baik, sedang,ÃÂ rusak dan sangatÃÂ rusak, d) kendaraan umum penumpang, yangÃÂ terdiri dari MPUÃÂ (mobilÃÂ penumpangÃÂ umum)ÃÂ danÃÂ busÃÂ umumÃÂ d)ÃÂ angkutanÃÂ barangÃÂ (truk)ÃÂ e)ÃÂ kendaraanÃÂ pribadi yangÃÂ terdiriÃÂ dariÃÂ mobilÃÂ penumpang,ÃÂ bus,ÃÂ danÃÂ sepeda motorÃÂ f)ÃÂ panjangÃÂ trayekÃÂ angkutan ÃÂ umum. Pengaruh palingÃÂ tinggi dari struktur kotaÃÂ terhadapÃÂ konsumsi BBM adalah Jumlah penduduk yaitu 0,986. SistemÃÂ transportasiÃÂ ÃÂ ÃÂ kotaÃÂ juga mempunyaiÃÂ nilaiÃÂ pengaruhÃÂ yangÃÂ tinggiÃÂ terhadapÃÂ konsumsi BBMÃÂ yaituÃÂ 0,907. StrukturÃÂ kota mempengaruhi ÃÂ konsumsi BBMÃÂ sangatÃÂ kuatÃÂ denganÃÂ nilaiÃÂ loading 0,976.ÃÂ HubunganÃÂ strukturÃÂ kotaÃÂ terhadapÃÂ konsumsiÃÂ BBMÃÂ lebihÃÂ kuatÃÂ dibandingÃÂ denganÃÂ sistem transportasi terhadap konsumsi BBM. Kata kunci: pengaruh, struktur kota, sistem transportasi, konsumsi BBM.